Impact of Daily Self-Care Schedule Intervention on Improving Self-Care Ability in Patients with Schizophrenia - Sari, Mertin Kartika; Fatmawati, Atikah; Prastya, Anndy (Jurnal Ilmiah Ners Indonesia, 2025)
Schizophrenia commonly reduces self-care abilities due to positive and negative symptoms and impaired executive function, which limit independence and quality of life. A structured daily schedule is a simple non-pharmacological strategy that may support routine formation and increase patient engagement. This study aimed to examine the effect of a daily nursing schedule on the self-care abilities of patients with schizophrenia. A quasi-experimental pre-test and post-test control group design was used with 35 respondents. The intervention group received a structured daily self-care schedule for six days. Self-care independence was measured using an observation sheet adapted from the Indonesian Nursing Outcome Standards (SLKI) code L.11103 (Self-Care). Data were analyzed using the Wilcoxon Signed Rank Test. Results showed a significant improvement in the intervention group (p = 0.000), while the control group showed no significant change (p = 0.180). The daily schedule was effective because it provided structure, predictability, and clear expectations, allowing patients to build consistent habits and participate more actively in self-care tasks. The intervention also encouraged family involvement, strengthening external support, and reinforcing patient motivation. These findings indicate that a structured daily schedule can be integrated into psychiatric nursing practice as an effective and low-cost psychosocial intervention to enhance independence, reduce caregiver burden, and improve the quality of life of individuals with schizophrenia. Future studies are recommended to assess long-term outcomes, involve larger and more diverse samples, and explore the use of digital scheduling tools or structured family participation to optimize intervention results.